RANCANG BANGUN PROTOTIPE SISTEM PENDETEKSI ASAP ROKOK BERBASIS MIKROKONTROLER MENGGUNAKAN SENSOR MQ-2 DILENGKAPI DENGAN EXHAUST FAN - Ida Ayu Putu Intania Paramitha1; IGAK Diafari Djuni; Widyadi Setiawan (Jurnal SPEKTRUM, 2020)
This research is conducted to detect cigarette smoke based on a microcontroller usingMQ-2 sensor equipped with an exhaust fan. This system has three status namely good smokelevel, moderate smoke level and unhealthy smoke level. The concentration of smoke detectedcan be monitored by a smartphone, in which the system will send a message via telegramwhen the room is detected by cigarette smoke. Based on the research that has been done, thesystem made has been able to send the smoke concentration data to telegram, the detectedsmoke concentration level and turn on the buzzer and the DC Fan when the smokeconcentration status is in moderate level around 100 - 400 ppm and in unhealthy level around> 400 ppm. Furthermore, it has been also able to send the comparison of energyconsumption, when both of the fans are off, the energy consumption is 2.42 Wh, and whenboth of the fans are on, then the energy consumption is 9.44 Wh.